Pengaruh Pendidikan Agama Islam terhadap Toleransi Antarumat Beragama di Masyarakat - Erna Khairani; Syamsiah Depalina Siregar (PT. Willy Print Art, 2025)
Islamic Religious Education has a crucial role in forming the basis for religious tolerance amidst the diversity of society. This article explores how Islamic religious education not only conveys its own basic teachings, but also how to appreciate and respect other beliefs. By examining the history and basic principles of Islam which emphasize tolerance and peace, this article provides insight into how these teachings are reflected in the Islamic education curriculum. Through curriculum analysis and teaching methodology, this article reveals how the concept of tolerance is integrated in Islamic education, providing concrete examples of educational institutions that have successfully implemented this approach. Apart from that, this article also discusses the challenges faced in implementing tolerance education and potential solutions to overcome them. Emphasis is placed on the importance of educating the younger generation with a broad and inclusive understanding of religious tolerance as the key to creating a harmonious society. Through this approach, Islamic religious education can be an effective tool for overcoming prejudice and promoting understanding between religious.